2008
DOI: 10.1007/s12283-008-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Segmental sequencing of kinetic energy in a computer-simulated golf swing

Abstract: The concept of the transfer of kinetic energy (KE) sequentially through the human body from proximal to distal segments is an influential concept in biomechanics literature. The present study develops this area of research through investigation of segmental sequencing of the transfer of KE by means of computer simulation. Using a musculoskeletal computer model previously developed by the authors, driven using three-dimensional kinematic data from a single elite male golfer, combined inverse and forward dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
6
14
0
Order By: Relevance
“…The live golfer generated a clubhead speed at impact that was 0.04 m/s faster than that of the model. In terms of clubhead speed, the fit of this model to live golfer results appears as good as that of Kenny et al [18], who reported a RMSE of 1.93 m/s and a difference in peak clubhead speed of 1.99 m/s. The fit of the 3D trajectory data reported by Kenny et al appears to be in spherical coordinates making it difficult to compare with our results.…”
Section: Model Validationsupporting
confidence: 73%
See 1 more Smart Citation
“…The live golfer generated a clubhead speed at impact that was 0.04 m/s faster than that of the model. In terms of clubhead speed, the fit of this model to live golfer results appears as good as that of Kenny et al [18], who reported a RMSE of 1.93 m/s and a difference in peak clubhead speed of 1.99 m/s. The fit of the 3D trajectory data reported by Kenny et al appears to be in spherical coordinates making it difficult to compare with our results.…”
Section: Model Validationsupporting
confidence: 73%
“…While the forward model served as verification to Nesbit's data collection and analysis procedure, it appears his results could have been generated with an inverse dynamics model alone. Recently, Kenny et al [18] conducted a study, with a methodology similar to that of Nesbit, to investigate the transfer of kinetic energy through the golfer. Kenny et al's methodology included an extra step which involved using the captured 3D kinematic data to ''train'' muscle joint torques in a golfer model.…”
Section: Introductionmentioning
confidence: 99%
“…However, the sequence at which the maximum angular velocities occur is not the same for all subjects. The results of Kenny et al [19] for segmental sequencing of kinetic energy in a computer-simulated golf swing indicate a subjective optimal coordination of sequencing, reinforcing the benefit of single-subject in their analysis of the golf swing. Putnam et al [18] showed kinematic sequencing.…”
Section: Relative Magnitude and Sequence Of Maximum Angular Velocitymentioning
confidence: 77%
“…Kenny et al 35 developed and validated a full-body computer simulation for a golfer using the driver club and seven-iron and also a driver-specific model to investigate the effects of using longer shafts for the drive shot. 36 Kenny et al 35,36 found that when using longer drivers, both club head and ball velocities along with ball carry (total ball distance) tend to increase with no loss of accuracy. Concomitantly, models were able to ascertain that while more effort is required to swing the longer driver, muscle force increments were realistically achievable.…”
Section: Figurementioning
confidence: 99%